Determinants of Controlling in Foreign Subsidiaries of MNEs: On the Explanatory Potential of the Institutional Perspective - Cezary Kochalski; Magdalena Łuczak-Trąpczyńska (Entrepreneurial Business and Economics Review)
Objective: The main aim of this paper is to identify gaps in extant literature on controlling in MNEs, in particular factors affecting related managerial decisions. Secondly, the relevance of the institutional perspective will be examined for its potential to explain the design of controlling in foreign subsidiaries.